Reacting to the Past and Role-Playing Games in Early Modern History - Fehleison, Jill (The sixteenth century journal, 2019)
The author explores how history is portrayed in role-playing game Reacting to the Past, developed by Mark C. Carnes of Barnard College. Topics include how the game has spread since 2001, its interdisciplinary nature in depicting the early modern period, and how it portrays various historic aspects including slavery, race, religion, gender relations, Imperialism, genocide, the environment, nation-building, politics, and medicine.